ANTI-BCG Immunohistochemical Detection of Mycobacteria in Formalin-Fixed Paraffin-Embedded Tissue Samples if Granulomatous Lymphadenitis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objective: In order to improve the diagnosis of extrapulmonary tuberculosis (EPTB). The present study has designed to evaluate the applicability of immunohistochemistry (IHC) by using polyclonal anti-BCG (Bacillus Calmette Guérin) antibody on tissue sections for detection of tuberculous bacilli or their components in granulomatous lymphadenitis and to assess its advantages over conventional Ziehl Neelsen (ZN) histochemical staining.Materials and Methods: A retrospective study of forty one formalin-fixed and paraffin-embedded (FFPE) biopsies of tuberculous granulomatous lymphadenitis, randomly selected from the archives of pathology laboratories in Erbil during the period from 2009 -2012. All specimens were subjected to ZN staining for acid fast bacilli (AFB) and IHC staining by polyclonal anti-BCG antibody; then a comparison of the detection rate of both techniques was done.Results: AFB were identified by ZN stain in 27/41 (65.9%) of the cases; while IHC staining was positive in 39/41 (95.1 %) of cases.Conclusion: IHC is a simple, sensitive and useful diagnostic technique, superior to conventional ZN staining, in detection of mycobacterium bacilli or their components in granulomatous lymphadenitis.